Предмет: Математика,
автор: janka5555
7х-(3+2х)=х+9
13-(2х-5)=х-3
3х-(10-9х)=22х
26-(17-2х)=5х
Ответы
Автор ответа:
0
7х-3-2х=х+9
7х - 2х - х = 9 + 3
4х = 12
х = 3
============================
13 - 2х + 5 = х - 3
- 2х - х = - 13 - 5 - 3
- 3х = - 21
х = 7
=============================
3х - 10 + 9х = 22х
3х + 9х - 22х = 10
- 10х = 10
х = - 1
=============================
26 - 17 + 2х = 5х
2х - 5х = 17 - 26
- 3х = - 9
х = 3
7х - 2х - х = 9 + 3
4х = 12
х = 3
============================
13 - 2х + 5 = х - 3
- 2х - х = - 13 - 5 - 3
- 3х = - 21
х = 7
=============================
3х - 10 + 9х = 22х
3х + 9х - 22х = 10
- 10х = 10
х = - 1
=============================
26 - 17 + 2х = 5х
2х - 5х = 17 - 26
- 3х = - 9
х = 3
Похожие вопросы
Предмет: Математика,
автор: danildrogot
Предмет: Музыка,
автор: matveynikolaev10
Предмет: География,
автор: Аноним
Предмет: Биология,
автор: 89043040905
Предмет: Математика,
автор: mishafonin